The Social Integration of Immigrants and the Role of Policy – A Literature Review - Nadzeya Laurentsyeva; Alessandra Venturini (Intereconomics, 2017)
As with economic integration, immigrants' social integration improves along with their years of residence in destination countries. Policies have some potential to influence the process of social integration.
Keywords: 330